Mute Swan flocks - Minton, C D T (Wildfowl, 1971)
This paper considers all aspects of the nature and function of the Mute Swan Cygnus olor flocks in a 550 sq. mile (1,440 sp. km.) area of south Staffordshire studied from 1961-1971. During this period the flock population has declined at an average of 5-6% per year and several of the smaller flocks have disappeared. With the spring paired population decreasing at an average of only 1% per year there has been a change from nearly two-thirds of the population being unpaired each spring in the early years to less than a half in recent years. The age structure of the flocks at various times of the year has been detailed and major differences between flocks illustrated. Birds which have previously been paired occur in the flocks at all times of the year, being at a peak in the summer moulting congregations. Swan movements are mainly governed by a reluctance to traverse ground above 500 feet (152 m.) and a strong preference to travel along river valleys and low ground below 250 feet (76 m.). Significant interchange takes place between flocks up to about 15 miles (24 km.) apart, but only about 5% of the population moves further than 30 miles (48.2 km.) and only 1-2% more than 50 miles (80.4 km.). The majority of long movements take place in the first two years of life, particularly the second year. Regular movements to special moulting sites occur annually. The oiling disaster at Burton-on-Trent in July 1966 wiped out a large proportion of the resident flock and the subsequent gradual recovery of numbers has been recorded. The total population in the study area may now have stopped declining.